Parametric study of vertical axis wind turbine rotor configurations using CFD - Difuntorum, John Keithley L.
Vertical Axis Wind Turbines (VAWT) remain a potential candidate for renewable energy generation especially in the built environment. However, their viability is largely dependent on maximizing energy extraction. Studies on various VAWT design parameters have been conducted to determine which configuration will yield the best performance. A consolidated research on the effects of these turbine design parameters is then necessary to optimize VAWT design and operation systematically. This study examines the effects of varying VAWT design parameters such as airfoil mounting position, airfoil fixing angle, and rotor solidity on VAWT performance. Numerical analysis using Computational Fluid Dynamics were employed to model VAWT operation on steady wind. For further understanding of VAWT aerodynamics, flow vorticity visualizations and blade force metrics were analyzed. Results show that marginal improvements are observed when the mounting position is adjusted towards the trailing edge. Incorporating a negative fixing angle on the airfoil also improves VAWT performance. Lastly, the number of blades on VAWT determines the tip-speed ratio range on which to operate it. 2-blade VAWTs prefer higher TSRs, 3-blade VAWTs operate on median TSRs, and 4-blade VAWTs peak on lower TSRs.